Crystal Engineering In Antisolvent Crystallization Of Neodymium Sulfate - Sibanda, Jonathan (Department of Chemical Engineering, 2024)
Antisolvent crystallization is a separation technology that separates a solute from the solvent by the addition of another solvent, in which the solute is sparingly soluble. High yields are achieved by using higher antisolvent-to-solvent ratios, but this generates higher supersaturation, which causes excessive nucleation. This results in the production of smaller or finer particles, which are difficult to handle in downstream processes such as drying and filtration. Therefore, this study aimed at investigating the effect of varying the organic (antisolvent)-toaqueous ratio and seed loading on the yield, particle size distribution, and morphology of neodymium sulfate octahydrate product, during its recovery from an aqueous leach solution using antisolvent crystallization. A batch crystallizer was used for the experiments, while ethanol was used as the antisolvent. Neodymium sulfate octahydrate [Nd2(SO4)3.8H2O] seeds obtained from antisolvent crystallization at a lower organic-to-aqueousratio of 0.4 were used to investigate the effect of seed loading. The crystals exhibited a plate-like morphology, with the plates becoming thinner, rounded, and layered at higher organic-to-aqueous ratios. This was attributed to enhanced physical interactions between the ethanol and the growing crystals, which possibly caused the ethanol to be adsorbed onto the crystalline surfaces, thereby inhibiting growth from one plane to another. The final particle size distribution curves shifted showing an increase in the particle sizes as the organic-to-aqueous ratio was increased from 0.8 to 1.4. The mean particle size increased from 106.1µm at an organic-to-aqueous ratio of 0.8 to 141.4 µm at an organic-to-aqueous ratio of 1.4. This was attributed to the agglomeration of smaller or fine particles that formed at high supersaturation into bigger particle sizes. The total number of particles decreased while the total volume increased as the organic-to-aqueous increased from 0.8 to 1.4. As the organic-to-aqueousratio increased from 0.8 to 1.4, the final product yield increased from 44% to 90%. The increase in yield was attributed to the increased interaction of ethanol molecules with the solvent molecules, which reduced the solubility of neodymium sulfate. Increasing the seed loading above the critical seed loading of 2.98% to 20% resulted in smaller final particle sizes of 101.5 µm compared with 165.8 µm obtained when the system was not seeded. These smaller sizes obtained at seed loadings above the critical seed loading had narrow particle size distributions. The span of the particle size distribution for the unseeded case was 1.54 while for PSDs obtained at seed loadings above the critical seed loading was less than 1.30. Seeding improved the filtration performance by 47%. This was due to the narrow particle size distribution and improved crystal morphology. It is recommended that to obtain higher yields and particles with unimodal particle size distribution, higher organic-to-aqueous ratios above 1.2 be used, and seeding be conducted at seeding loadings above the critical seed loading. In addition, if crystals of well-defined or faceted morphology are required it will be reasonable to use a lower organic-to-aqueous ratio such as 0.6 to 0.8 at batch times greater than 2.5 h. The filterability of neodymium sulfate at higher organic-to-aqueous ratios needs to be investigated for future studies.